1992
DOI: 10.1080/02724936.1992.11747544
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity of high dose salicylate therapy in acute rheumatic fever

Abstract: Liver function tests, including serum alanine aminotransferase (ALT) activity, serum bilirubin, alkaline phosphatase, serum proteins, blood ammonia levels and intravenous glucose utilization, were monitored in 50 children with acute rheumatic fever receiving anti-rheumatic doses of aspirin. There was a significant increase in blood ammonia levels and serum ALT after aspirin therapy. A significant fall in glucose utilization coefficient was also recorded. Serum alkaline phosphatase, bilirubin and total proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
4

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
2
0
4
Order By: Relevance
“…found that hepatotoxicity occurred in 17% of patients with ARF 8 . In another study, this rate was found to be 24% 9 . Arthreya et al.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…found that hepatotoxicity occurred in 17% of patients with ARF 8 . In another study, this rate was found to be 24% 9 . Arthreya et al.…”
Section: Discussionmentioning
confidence: 91%
“…It is a potent analgesic, antipyretic and anti‐inflammatory agent, exerting its anti‐inflammatory effect by inhibition of cyclo‐oxygenase. The pediatric dose is approximately 25 mg/kg per day (range 15−30 mg/kg per day) 8,9 . Tolmetin seldom produces marked elevations of the transaminase enzymes observed with aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…İlaca bağlı hepatotoksisite tanısı için ALT düzeyinin normalin en az iki katı kadar yükselmiş olması ve diğer nedenlerin ekarte edilmesi gerekir [11]. Akut romatizmal ateşli hastalarda aspirine bağlı hepatotoksisite sıklığı değişik çalışmalarda %17 ile %50 arasında değişen oranlarda bildirilmiştir [7,18,19]. Ülkemizden yapılan çalışmalarda da %24-%42,6 gibi yüksek oranlar bildirilmektedir [11,[20][21][22].…”
Section: Discussionunclassified
“…Asetilsalisilik asite bağlı hepatotoksisite gelişme riski çocuklarda erişkinlere göre daha yüksektir (4)(5)(6).…”
Section: Introductionunclassified
“…Salisilata bağlı hepatotoksisite, genellikle hepatoselüler nekroz şeklinde ve doza bağımlı olarak meydana gelir, ilacın kesilmesiyle olguların büyük kısmında geriye dönüşümlüdür. Asetilsalisilik asite bağlı hepatotoksisite, asemptomatik hafif karaciğer enzim yüksekliğinden sarılığın eşlik ettiği ağır hepatite hatta karaciğer yetmezliğine kadar değişen şiddetteki klinik tablolarda görülebilir(5,6,9). Bizim olgumuzda da herhangi bir semptom olmadan karaciğer enzimlerinde 30 kata kadar varan bir artışın olduğu hepatotoksisite tespit edilmiştir.…”
unclassified